Diallyl trisulfide, a H2S donor, inhibits cell growth of human papillary thyroid carcinoma KTC‐1 cells through a positive feedback loop between H2S and cystathionine‐gamma‐lyase. (26th January 2020) - Xu, Shichen; Pan, Jie; Cheng, Xian; Zheng, Jiangxia; Wang, Xiaowen; Guan, Haixia; Yu, Huixin; Bao, Jiandong; Zhang, Li
Abstract : Diallyl trisulfide (DATS), derived from garlic, is a well‐known hydrogen sulfide (H2 S) donor. H2 S has recently emerged as a novel gasotransmitter involved in the regulation of cancer progression. The present study demonstrated that DATS along with other two H2 S donors, NaHS and GYY4137, significantly inhibited papillary thyroid carcinoma KTC‐1 cells growth. DATS treatment triggered a rapid H2 S generation within 5 min in KTC‐1 cells. Iodoacetamide, a potent thiol blocker reagent, partially rescued the cell membrane damage and ultimate cell death induced by DATS, indicating H2 S contributed to the apoptosis‐inducing efficacy of DATS on thyroid cancer cells. Specifically, DATS treatment significantly upregulated the expression and enzymatic activity of cystathionine gamma‐lyase (CTH), one of H2 S‐producing enzymes, which was responsible for endogenous H2 S generation. After DATS treatment, H2 S quickly permeated cell membranes and activated NF‐κΒ/p65 signaling pathway in KTC‐1 cells. Nuclear translocated NF‐κB bound to the promoter of CTH to enhance its transcription. These evidences proved that exogenous H2 S elevated CTH expression. CTH, in turn, catalytically generated a much higher level of endogenous H2 S. This positive feedback sustained excess H2 S production, which resulted in PTC cells growth inhibition. These findings may shed light on the development of novel H2 S‐based antitumor agents. Abstract :